2023
DOI: 10.36922/gtm.288
|View full text |Cite
|
Sign up to set email alerts
|

Antisense oligonucleotides targeting hepatic angiotensinogen reduce atherosclerosis and liver steatosis in hypercholesterolemic mice

Abstract: Hepatocyte-derived angiotensinogen (AGT) is the precursor of angiotensin II (AngII). We determined the effects of hepatocyte-specific (N-acetylgalactosamine-conjugated) antisense oligonucleotides targeting AGT (GalNAc AGT ASO) on AngII-mediated blood pressure (BP) regulation and atherosclerosis and compared its effects with losartan, an AngII type 1 (AT1) receptor blocker, in hypercholesterolemic mice. Eight-week-old male low-density lipoprotein (LDL) receptor deficient mice were administered vehicle or GalNAc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Inhibition of renin would have an equivalent effect of AGT deletion on diminishing synthesis of all angiotensin peptides while retaining AGT in plasma, while inhibition of AT1 receptors blocks AngII-AT1 receptor interaction and their downstream signaling. 46,65 A second line of evidence for AngII-independent effects was demonstrated in hepatocyte-specific AGT-deleted mice in which plasma concentrations of AGT were restored by infection with adenoassociated viruses expressing either Agt or des(AngI)Agt . Expression of both forms of AGT resulted in equivalent restoration of body weight gain and liver steatosis.…”
Section: Agt In Cardiovascular and Metabolic Diseasesmentioning
confidence: 99%
See 4 more Smart Citations
“…Inhibition of renin would have an equivalent effect of AGT deletion on diminishing synthesis of all angiotensin peptides while retaining AGT in plasma, while inhibition of AT1 receptors blocks AngII-AT1 receptor interaction and their downstream signaling. 46,65 A second line of evidence for AngII-independent effects was demonstrated in hepatocyte-specific AGT-deleted mice in which plasma concentrations of AGT were restored by infection with adenoassociated viruses expressing either Agt or des(AngI)Agt . Expression of both forms of AGT resulted in equivalent restoration of body weight gain and liver steatosis.…”
Section: Agt In Cardiovascular and Metabolic Diseasesmentioning
confidence: 99%
“…3,4 Unexpectedly, these studies demonstrated profound effects of liver-derived AGT deletion on the development of Western diet-induced body weight gain and liver steatosis in normocholesterolemic or hypercholesterolemic mice. 3,46,65 These effects are not mimicked by pharmacological inhibition of AT1 receptors, ACE, or renin, and hence suggest that liver-derived AGT exerts effects that are independent of reduction in AngII production. 3,46,65 Demonstration of liver-derived AGT's ability to contribute to disease has facilitated interest in inhibiting AGT synthesis using ASO or small-interfering RNA (siRNA).…”
Section: Manipulation Of Agt Synthesis By Genetic and Pharmacological...mentioning
confidence: 99%
See 3 more Smart Citations